2016
DOI: 10.1159/000441783
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of Laparoscopic or Robotic Adenomyomectomy with or without Medical Treatment for Severely Symptomatic Adenomyosis

Abstract: Background/Aims: To determine the long-term efficacy of laparoscopic or robotic adenomyomectomy with or without gonadotropin-releasing hormone (GnRH) for the treatment of severely symptomatic adenomyosis. Methods: Between August 2008 and May 2011, we prospectively observed 33 patients who underwent laparoscopic or robotic adenomyomectomy with uterine artery ligation for the treatment of symptomatic adenomyosis. Seventeen patients (52%) received 3-course GnRH agonist treatment after the adenomyomectomy. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…The traditional hysterectomy remains the main therapeutic strategy in the long term. However, considering the relevant technical progress of conservative surgical techniques in recent years and the expansion of lesion removal, the short‐term efficacy of conservative surgical techniques is significant in improving adenomyosis‐related dysmenorrhea and abnormal uterine bleeding 17 …”
Section: Discussionmentioning
confidence: 99%
“…The traditional hysterectomy remains the main therapeutic strategy in the long term. However, considering the relevant technical progress of conservative surgical techniques in recent years and the expansion of lesion removal, the short‐term efficacy of conservative surgical techniques is significant in improving adenomyosis‐related dysmenorrhea and abnormal uterine bleeding 17 …”
Section: Discussionmentioning
confidence: 99%
“…The mean operative time was 159.25 minutes, and the EBL was 117.5 mL. Chong et al [13] reported long-term efficacy in 8 cases of robotic adenomyomectomy. The authors excised 78.0 g of adenomyotic tissue and the operative time was 204.2 minutes, and EBL was 48 mL.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have compared surgical outcomes between robotic and laparoscopic surgeries. Chong et al [13] reported a longer operative time but similar length of hospitalization and EBL in the robotic versus the laparoscopic adenomyomectomy group. [13] In addition, suturing time was significantly longer in the robotic than in the laparoscopic adenomyomectomy group (79.8 ± 23.4 vs 39.7 ± 17.9 min, P < .001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, minimally invasive procedures may be used to treat ADS. In a recent study it was estimated that laparoscopic or robotic adenomyomectomy was feasible and safe for women with severely symptomatic ADS who requested uterine preservation (19). ADS does not usually cause marked pathological changes in the serosa of the uterus.…”
Section: Discussionmentioning
confidence: 99%